Social Support and Posttraumatic Stress Disorder in combat veterans in Croatia - Jelušić, Ilijana; Stevanović, Aleksandra; Frančišković, Tanja; Grković, Jasna; Šuković, Zoran; Knezović, Zvonimir (2010)
Recent studies have shown that greater social support after combat stress is associated with better psychological posttraumatic outcomes. By comparison of a group of veterans (n=71) who sought psychiatric help and were diagnosed with PTSD (clinical group) and a group of veterans (n=43) without PTSD (control group) we examined various components of structural and functional social support in war veterans in Croatia. The measures of social support were assessed for two time periods: a) immediately after the war, and b) at the present time. Results of two-way analysis of variance indicate that veterans without PTSD tend to report significantly higher number of persons who provide them different forms of social support than veterans with PTSD. Perceived family and friends support is higher in veterans without PTSD than in veterans with PTSD. Support received from friends and fellow soldiers decreases over time in both groups, whereas for the clinical group support of friends decreases significantly more.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG